Analisis Manajemen Sumber Daya Manusia Prspektif Pelatihan dan Pengembangan Tenaga Kerja - Edi Saputro, Ristanto (INAIFAS Press, 2021)
In the era of information and digitalization, world business competition is getting bigger. Every company needs to develop its products all the time. Even the product must be predictable in the future. In addition, the use of tools and machines in the company must also measure so that the quality and quantity of the product can meet market standards. In a company must have human resources / workforce who have good skills and knowledge. The problem arises if the workforce owned by the company does not fulfill the two aspects above. Therefore companies need to carry out training and development to develop skills and knowledge of the workforce. There are many benefits to a company that carries out training and workforce development Keywords: HR, training, development, workforce